Toxoplasmosis-Serological Evidence and Associated Risk Factors among Pregnant Women in Southern Thailand - Nissapatorn, V.; Suwanrath, C.; Sawangjaroen, N.; Ling, L.Y.; Chandeying, V. (American Society of Tropical Medicine and Hygiene, 2011)
Abstract. Toxoplasma gondii is an important parasite in pregnant women. This case-controlled study assessed the seroprevalence of toxoplasmosis in 640 pregnant women in southern Thailand and identified their associated risk factors. The overall seroprevalence of toxoplasmosis was 181 (28.3%). Of this, 138 (21.6%) were positive for only anti-Toxoplasma immunoglobulin G (IgG) antibody, 43 (6.7%) were positive for both IgG and IgM antibodies, and none were positive for IgM antibody. Multivariate analysis revealed that increasing age (adjusted odds ratio [OR] = 1.64, 95% confidence interval [CI] = 1.01-2.67), living outside Songkhla province (adjusted OR = 1.56, 95% CI = 1.08-2.24), parity (adjusted OR = 1.65, 95% CI = 1.01-2.68), contact with cats (adjusted OR = 1.70, 95% CI = 1.20-2.43), and drinking of unclean water (adjusted OR = 1.70, 95% CI = 1.08-2.68) were factors associated with Toxoplasma seroprevalence. On the basis of the results obtained, a health surveillance program should be initiated as a primary preventive measure for congenital toxoplasmosis and focus on educating women of the child-bearing age group to avoid contact with cats and to strictly practice personal hygiene.